Upaya Meningkatkan Hasil Belajar IPA menggunakan Model Pembelajaran Direct Instruction (DI) Berbantuan Media Audio Visual pada Peserta Didik - Cancie Cancie; Ade Salahuddin Permadi (Bitnet: Jurnal Pendidikan Teknologi Informasi, 2018)
This research aims to improve the learning outcomes of science and describe the learning activities of students by using Direct Instruction learning models assisted by Audio Visual media on students. The research method used in this study was classroom action research (PTK). The research subjects were 27-grade SDN 3 Panarung students. The technique of collecting data uses observation and tests. The results of the study show that the learning activities of students become good. Teacher activities in the first cycle averaged 2.4 categories quite well and the second cycle averaged 3.5 good categories, while the activities of students in the first cycle averaged 2.6 categories enough and the second cycle averaged 3.1 categories well. There is an increase in science learning outcomes using the Direct Instruction (DI) learning model assisted by Audio Visual media in fourth grade students of SDN-3 Panarung Palangka Raya 2016/2017 school year with the results of analysis on the Pratindakan classical completeness which is 40.7% with an average value 65, the first cycle of classical completeness is 74% with an average value of 72, and classical completeness in cycle II is 100% with an average value of 87.5